Auditoria de control interno al área de tesorería y su relacion con la toma de decisiones del gobierno autónomo descentralizado municipal de Quevedo año 2013 - Yong Zambrano, Rudy Gabriela (2015)
This research has the incidence of internal control to treasury area where his most significant problem is the inadequate management of financial processes as there is a lack of knowledge. In Ecuador there are some laws and regulations of public sector framing the existence of a control system in subsidiaries government for this reason, this work is based on a system of indicators and design processes that optimize resources and improve productivity. This research project is composed of two segments, the first is the introduction and the second to the chapters on a number five constitute the body of the document. Practice is considered that the information necessary to achieve the stated objective was obtained directly from reality. To develop the theoretical framework of the research was necessary to analyze each of the variables that occur as a result of the problem statement, it was necessary to seek timely and accurate information on books, articles, brochures and websites, which I own concept met the technical requirements of scientific writing. In terms of research methodology, methods such as inductive, deductive and analytical were used, as I believe they are the most appropriate when executing an audit is about. As for the techniques, it became necessary to resort to the interview, as it is the most direct method for information. The execution of this work included evaluation of internal control by 20 questions. Regarding the level of trust we obtained 71.43%, so we have a 28.57% level of control risk; measuring risks are: 34% inherent risk; 28.57% control risk; and detection risk assumed 15%; resulting in 1.46% of audit risk. An essential part of this research project, conclusions and recommendations in Chapter V arise, these recommendations in my opinion contribute appropriately to the treasury department of the Autonomous Government of the Canton Municipal Decentralized Quevedo.